2003
DOI: 10.1590/s0004-282x2003000600002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intracranial hemorrhage and neonatal seizures on the neurological and psychomotor development of premature infants at Hospital de Clínicas de Porto Alegre, Brazil

Abstract: -This study compared the results of neurodevelopmental examination at 6 months' corrected age of premature infants with neonatal seizures and/or intracranial hemorrhage and normal premature infants. There was a statistically significant correlation (p=0.000007) between intracranial hemorrhage and seizures in the group of 68 premature infants seen in the neurodevelopmental outpatient service at Hospital de Clínicas de Porto Alegre, Brazil. Intracranial hemorrhage was significantly associated with multiparity (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
10

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
4
0
10
Order By: Relevance
“…This condition is complicated by acute seizures that commonly accompany ICH in children as well as adult patients 1–3. Newborns are at particularly high risk for ICH and seizures due to traumatic deliveries, stroke, subarachnoid and intraventricular hemorrhage, and vitamin K deficiency 4–6. Studies on premature infants show a highly significant correlation between intracranial hemorrhage and seizures 4, 7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is complicated by acute seizures that commonly accompany ICH in children as well as adult patients 1–3. Newborns are at particularly high risk for ICH and seizures due to traumatic deliveries, stroke, subarachnoid and intraventricular hemorrhage, and vitamin K deficiency 4–6. Studies on premature infants show a highly significant correlation between intracranial hemorrhage and seizures 4, 7.…”
mentioning
confidence: 99%
“…Newborns are at particularly high risk for ICH and seizures due to traumatic deliveries, stroke, subarachnoid and intraventricular hemorrhage, and vitamin K deficiency 4–6. Studies on premature infants show a highly significant correlation between intracranial hemorrhage and seizures 4, 7. Because seizures contribute to both mortality and morbidity, and patients with post‐ICH seizures have worse outcomes than ICH patients without seizures,2–4 understanding the cellular mechanisms responsible for the occurrence of seizures during ICH is important for developing proper medical treatment and management of ICH.…”
mentioning
confidence: 99%
“…Um terço dessas crianças melhorou sem a necessidade de terapia anticonvulsiva 20 . Ohlweiler et al encontraram um significativo comprometimento do desenvolvimento neurológico dos recém-nascidos com a idade corrigida de 6 meses com AVC hemorrágico através da análise de tônus muscular, reflexos, força e controle da cabeça 21 .…”
Section: Avc Isquêmico Perinatalunclassified
“…20 Ohlweiler et al found significant impairment in neurological development in neonates with HS analyzing muscle tone, reflexes, strength, and head control at 6 months of corrected age. 21 In newborn infants with HS, care should be taken to maintain platelets at normal levels while replacing coagulation factors and vitamin K in specific cases when necessary. Hydrocephalus is common after hemorrhagic events and must be managed using ventricular drainage if persistent or high volume.…”
Section: Perinatal Ischemic Strokementioning
confidence: 99%